Compreensão de direitos de aprendizagem por uma professora alfabetizadora : caminhos da prática docente para o trabalho com a leitura no ciclo de alfabetização - Barbosa, Áureo José (2017)
This research was developed within the Master Degree Program in Education of the Federal University of Mato Grosso, in Rondonópolis city (PPGEdu/UFMT/CUR), in the line of research Language, culture and knowledge construction process: historical and contemporary perspectives. It was constructed based on the discussions proposed within the research group Alphabetization and Scholar Literacy (ALFALE). This Masters’ thesis presents the results of an investigation about the learning rights within the literacy cycle. The research was developed with a literacy teacher who participated of PNAIC’s training and who teaches on the first phase of the first cycle in the earlier years of Elementary School at the Municipal School Sister Elza Geovanella, in Rondonópolis city. This is a qualitative research developed through a case study. The data collection methods applied in this study were systematic observation, semi structured interview (recorded and transcribed), printed questionnaire, fieldnotes and photographic registration. This investigation aims to analyze not only the understanding over the learning rights related to the reading process by the literacy teacher who participates of PNAIC, but also the implications of these conceptions on her pedagogical practice and work management. Besides, we tried to answer to the following questions: How does the teacher work is developed along daily routine, bearing in mind the reading learning rights? Does the understanding of the reading learning rights influence her pedagogical practice? As a legal basis reference, this study comprehends official documents published and institutionalized by the Ministry of Education as literacy public policies. Among them, we selected PNAIC’s official documents, theoretical and methodological notebooks used in teachers training and the document entitled as “Conceptual and methodological elements to Learning Rights definitions and Literacy Cycle Development (1st, 2nd and 3rd years) of Elementary School” (BRASIL, 2012a). As methodological basis to learning rights discussions, this investigation takes, among other authors, Cruz’s (2012) and Macedo’s (2013) theories. To promote a discussion over reading and teaching dimensions practicing, this investigation bases itself on the theories developed by Solé (2012), Kleiman (2013), Silva (1999; 2003), Zilberman (2008), Cosson (2012; 2017), Leal, Morais and Albuquerque (2010) and Guedes-Pinto (2016). The discussions about Literacy were developed through the theories proposed by Soares (2000; 2004), Rojo acher(2009), Magalhães et al. (2012), Gontijo (2002; 2014) and other authors. The research’s analysis showed that the teacher’s understanding over the learning rights influences the efficiency of reading practices in classroom and also encourages the construction of the children’s reader identity. Besides, the research showed that the learning rights were evinced by the teacher’s work, acting as a guiding instrument of pedagogical practices regarding its organization and also contributing to planning, evaluation and children’s learning monitoring.